Irritable Bowel Syndrome in medical students at a Peruvian university: a cross-sectional study - Quiroga-Castañeda, Pedro P.; Berrios-Villegas, Iván; Valladares-Garrido, Danai; Vera-Ponce, Víctor J.; Zila-Velasque, J. Pierre; Pereira-Victorio, César Johan; Valladares-Garrido, Mario J. (Frontiers in Medicine, 2024)
Background Irritable Bowel Syndrome has emerged as a significant public health challenge, particularly relevant in medical students due to the high demands of their studies, academic stress, and susceptibility to eating disorders. Nevertheless, conclusive evidence regarding the factors associated with Irritable Bowel Syndrome in the Latin American student population remains limited. The objective of this study was to determine the prevalence and factors associated with Irritable Bowel Syndrome in Human Medicine students at a university in northern Peru. Methods A cross-sectional analytical study conducted in Lambayeque, northern Peru. With 403 Human Medicine students (66.5% female, 33.5% male). A simple random probabilistic sampling type was used, based on a list of students enrolled. A multivariate analysis was conducted to determine the factors associated using simple and multiple regression models. Generalized Linear Models were applied, using the Poisson distribution family, robust variance, and the academic year as a cluster. Results The prevalence of Irritable Bowel Syndrome was 16.9% (95% CI: 13.37–20.86). The median age was 21 years, with 66.5% being female. In the multiple regression analysis, Irritable Bowel Syndrome was associated with a higher prevalence of depression (PR: 3.63; 95% CI: 1.26–10.49) and eating disorders (PR: 1.57; 95% CI: 1.01–2.43). For each additional year of age, the prevalence of Irritable Bowel Syndrome decreased by 9% (PR: 0.91; 95% CI: 0.83–0.99). Conclusion This study reveals that approximately two out of every 10 students exhibit symptoms related to IBS, underscoring its significance in the Human Medicine student population. Furthermore, depression and eating disorders were identified as significant factors associated with IBS in students. Consequently, it is essential to focus efforts on early identification and the implementation of preventive measures to mitigate the development of this pathology, given its substantial prevalence in this context of Human Medicine students.